Birth [videorecording (DVD)] - Glazer, Jonathan; Kidman, Nicole, 1967-; Bacall, Lauren, 1924-2014; Huston, Danny, 1962-; Heche, Anne (New Line Home Entertainment, 2005)
A widow for ten years, Anna is looking forward to getting remarried when a mysterious boy appears claiming to be the reincarnation of her late husband.